Acinetobacter baumannii: por que novos antibióticos são necessários ? - Rios, Ana Luisa Villa (2021)
Acinetobacter baumannii, an opportunistic gram-negative coccobacillus bacterium belonging to the genus Acinetobacter, has gained worldwide importance as a public health problem. This bacterium has an extraordinary ability to remain in the environment for long periods, and to acquire and regulate resistance mechanisms, causing several healthcare-related infections, such as ventilator-associated pneumonia and bacteremia. For a long time, beta-lactam antibiotics were used to treat infections caused by this bacteria. However, isolates that had resistance mechanisms, such as the production of enzymes that alter or inactivate the drug, were emerging and spreading across the globe due to the excess and misuse of antimicrobials. As of the 1990s, the first carbapenem-resistant A. baumannii isolates appeared, limiting the options available for the treatment of infections caused by this bacterium and increasing mortality rates. The World Health Organization classified as critical the urgent need to develop new antibiotics to treat infections caused by carbapenem-resistant A. baumannii. Currently, there are few treatment options on the market or under development for A. baumannii infections, such as polymyxins, tigecycline, eravacycline and cefiderocol; and there are only ten possible drugs in the 2021 antibiotic pipeline. Given the limited treatment option and reduced pipeline, and given the urgency of meeting the current and future needs of patients, it is necessary to prevent the emergence and spread of resistant microorganisms, and encourage and invest in a more robust pipeline to overcome the emergence of bacterial resistance so that there are antibiotics on the market that are effective against infections.